2015
DOI: 10.1371/journal.pone.0128199
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Thermotoga maritima Class III Ribonucleotide Reductase Lacks a Radical Cysteine Pre-Positioned in the Active Site

Abstract: Ribonucleotide reductases (RNRs) catalyze the reduction of ribonucleotides to deoxyribonucleotides, the building blocks for DNA synthesis, and are found in all but a few organisms. RNRs use radical chemistry to catalyze the reduction reaction. Despite RNR having evolved several mechanisms for generation of different kinds of essential radicals across a large evolutionary time frame, this initial radical is normally always channelled to a strictly conserved cysteine residue directly adjacent to the substrate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Until recently it was thought that all class III RNRs used formate as the reductant for ribonucleotide reduction and utilized a conserved set of active site residues, but recent phylogenetic analyses on class III RNRs (Wei et al , 2014a, Aurelius et al , 2015) and a metabolic pathway analysis (Wei et al , 2015) have suggested that this is not the case. Currently, it appears that there are at least three subclasses of NrdDs, which can be distinguished by the presence or absence of 3–4 catalytic residues and the requirement for formate as the reductant.…”
Section: Gre Ribonucleotide Reductasesmentioning
confidence: 99%
“…Until recently it was thought that all class III RNRs used formate as the reductant for ribonucleotide reduction and utilized a conserved set of active site residues, but recent phylogenetic analyses on class III RNRs (Wei et al , 2014a, Aurelius et al , 2015) and a metabolic pathway analysis (Wei et al , 2015) have suggested that this is not the case. Currently, it appears that there are at least three subclasses of NrdDs, which can be distinguished by the presence or absence of 3–4 catalytic residues and the requirement for formate as the reductant.…”
Section: Gre Ribonucleotide Reductasesmentioning
confidence: 99%
“… (1) Two recent independently solved structures of Thermotoga maritima class III RNR lack a suitably positioned cysteine [ 45 , 46 ]. Further work is required to determine the mechanistic details of the protein.…”
Section: Origin Of the Urrnrmentioning
confidence: 99%
“…Adding further mystery to the class III reaction mechanism, even the unanimous presence of the radical cysteine has been called into question by two recent independent crystal structures of T. maritima class III RNR [ 45 , 46 ]. At the position of the canonical radical cysteine is an isoleucine in both structures.…”
Section: Origin Of the Urrnrmentioning
confidence: 99%
See 1 more Smart Citation
“…In all three RNRs, allosteric regulation involves binding of the dNDP/dNTP products at a 4-helix bundle, involving two helices from each monomeric subunit, at the dimer interface of the enzyme ( Uhlin and Eklund, 1994 ; Larsson et al, 2001 ). The allosteric regulation causes conformational changes at a highly conserved 10 stranded α/β barrel where the active site “finger loop” structure resides in its center, or is brought to its center upon activation ( Aurelius et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%